Optimization of Entrepreneurship in Realizing the Profile of Pancasila Students at SMA Negeri 13 Pekanbaru Riau Province - Rahmatul Hadi; Heldi , Heldi; Yahya Yahya; Elida, Elida (CV. AFDIFAL MAJU BERKAH, 2023)
Realizing a Pancasila student profile, of course, cannot be separated from the support of various parties in producing superior students. But so far students' interest in entrepreneurship has not been optimal and needs to be improved. One form of project activities that exist in each school that can shape the national character to achieve student profiles in Pancasila is by instilling an entrepreneurial spirit. The purpose of this study is to contextually describe optimizing entrepreneurship in realizing the Pancasila student profile. The research method used is the descriptive qualitative method. In collecting data, researchers directly interact with informants using an interview guide. Based on the results of data analysis it can be concluded that schools that apply the independent curriculum can provide opportunities for students to develop an entrepreneurial spirit through Strengthening the Pancasila Profile with the theme of entrepreneurship, in this case, the teacher as a facilitator has optimal competence in entrepreneurship besides students gaining entrepreneurial knowledge and skills in playing an active role in the Pancasila Profile with the entrepreneurial theme.